Extraction of bio - oil rich in omega 3-6 fatty acid using different methods from heterotrophic marine microalga Schizochytrium mangrovei - Thom, Le Thi; Ha, Nguyen Cam; Hong, Dang Diem (Academia Journal of Biology, 2017)
In recent years, producing bio-oil from microalgae has gained increasing interest. Schizochytrium mangrovei is a heterotrophic marine microalga that is capable of producing high levels of biomass and lipid. In this study, S. mangrovei strain TB17 was investigated for production of bio-oil consist of omega 3-6 fatty acids using different methods, including a one-stage (direction transesterification of biomass) or a two-stage method (crude oil extraction followed by transesterification). In the one-stage method, omega 3-6 fatty acid alkyl esters (FAAE) extracted from dried biomass reached to 96.36% of total fatty acids (TFA), and 12.71% of dry cell weight (DCW) in which content of docosahexaenoic acid (C22: 6ω-3, DHA), eicosapentaenoic acid (C20: 5ω-3, EPA) and docosapentaenoic acid (C22: 5ω-6, DPA) was accounted for 85.01% of TFA. However, using fresh biomass as feedstock was resulted in lower yield of FAAE (90.95% of TFA and 3.26% of DCW). In the two-stage method, when fresh and dried biomass were used as feedstock, omega 3-6 free fatty acids (FFA) were obtained with equivalent yield (99.07% and 99.83% of TFA; 17.09% and 14.85% of DCW, respectively) with DHA, EPA and DPA contents accounting for over 80% of TFA. Thus, fresh biomass could also be used to extract bio-oil instead of dried biomass. These results would contribute to reduce manufacturing cost of the bio-oil rich in omega 3-6 fatty acids from Schizochytrium in the future. Citation: Le Thi Thom, Nguyen Cam Ha, Dang Diem Hong, 2017. Extraction of bio - oil rich in omega 3-6 fatty acid using different methods from heterotrophic marine microalga Schizochytrium mangrovei. Tap chi Sinh hoc, 39(3): 359-366. DOI: 10.15625/0866-7160/v39n3.9829. *Corresponding author: ddhong60vn@yahoo.com Received 18 May 2017, accepted 20 August 2017